APLIKASI ULANG AZOSPIRILLUM TERSELEKSI PADA TANAMAN CABAI MERAH (Capsicum annum, L) YANG DITANAM PADA ULTISOL - Imra Atil Mardya; Gusmini Gusmini; Agustian Agustian (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2020)
The endophytic bacteria are bacteria whose life cycle is partially or completely associated in the host plant tissue in various kinds of relationships (symbiosis) that it undergoes. The potential of endophytic bacteria as microbial resources is widely used as a biological control for plants, including as the producer of phytohormones and the agent of biocontrol and biofertilizer. This study aims to test selected endophyte bacterial isolates from chili as a biofertilizer to meet the nutrient requirements that are useful during the vegetative growth period of red chili in Ultisols. The study used a completely randomized design with 4 treatments and 3 replications, namely A = fertilizer N recommendation; B = Azospirillum sp AK+ Fertilizer N recommendation; C = Azospirillum sp BT+ Fertilizer N recommendation; D = Azospirillum sp DN+ fertilizer N recommendation. Azospirillum sp AK and Azospirillum sp DN isolates gave better vegetative growth than those of Azospirillum sp BT isolates with average dry weight, respectively, 19.49 g and 18.93 g and with a height of 29.67 cm and 29.60cm. The superiority of the 2 isolates was also shown in the observation of the number of leaves 30.39 and 22.50 and the number of branches 6.45 and 6.28 respectively for Azospirillum sp AK and Azospirillum sp DN isolates.Key words : Endophytic bacteria, red chili, Ultisols